Pengaruh Pendekatan Computational Thinking Berbasis Model Problem Based Learning pada Pembelajaran Membaca Teks Informasi Siswa Kelas V Sekolah Dasar: Pengaruh Pendekatan Computational Thinking Berbasis Model Problem Based Learning pada Pembelajaran Membaca Teks Informasi Siswa Kelas V Sekolah Dasar - Auliya Dwi Cahyani, Auliya; Sri Sumartiningsih; Panca Dewi Purwati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The transformation of education in the digital era requires mastery of 21st-century competencies, along with computational thinking and reading literacy skills that support each other. However, the reading comprehension ability of elementary school students in Indonesia remains relatively low, particularly in understanding complex informational texts. This study aims to analyze the effect of the Computational Thinking (CT) approach based on Problem-Based Learning (PBL) on fifth-grade elementary students’ ability to comprehend informational texts. The study employed a quantitative approach with a quasi-experimental design consisting of two groups: an experimental group using the CT-based PBL approach and a control group taught through conventional methods. Data were collected through reading comprehension tests covering literal, inferential, and critical aspects, and analyzed using t-tests and effect size calculations. The results revealed a significant difference between the two groups, with the experimental group showing greater improvement, especially in inferential and critical comprehension. These findings confirm that integrating CT into the PBL model can be utilized to enhance reading literacy and systematic thinking skills. From an instructional innovation perspective, this approach can serve as an innovative alternative to equip students with the necessary competencies to face the challenges of 21st-century learning.